The Strategy Group Analysis of the New York State Budget Situation (Tufts Archival Research Center, 2007)
Tobacco Industry Labor Management Committee analysis of the New York State Budget situation. Reviews fiscal position of the state and lays out options to raise new revenue. Asseses the political motivation of the Governor and legislature. Analyzes major labor and public interest groups who affect the budget process. Concludes that the tax fight in NY boils down to the status of the Personal Income Tax Cut.